If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -14 + -13 + -1y = -9 + 15 Reorder the terms: -14 + -13 + 4y + -1y = -9 + 15 Combine like terms: -14 + -13 = -27 -27 + 4y + -1y = -9 + 15 Combine like terms: 4y + -1y = 3y -27 + 3y = -9 + 15 Combine like terms: -9 + 15 = 6 -27 + 3y = 6 Solving -27 + 3y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 3y = 6 + 27 Combine like terms: -27 + 27 = 0 0 + 3y = 6 + 27 3y = 6 + 27 Combine like terms: 6 + 27 = 33 3y = 33 Divide each side by '3'. y = 11 Simplifying y = 11
| 3rs-6r+3s-7rs+10r-3s= | | 7x+9+8x-4= | | G=5g+5u | | 8x+1=-x-1 | | 9x+10x= | | 2y^2-8y+15-13y^2-8y+1= | | 4b-23=23-4b | | -8+5-3y=6y+7+4y | | 15(r-2)-4(r+4)=7 | | -11-7x+9x=-1-5+3+5x | | x^2-20x+91=0 | | 10-3d=4+2d | | a^2-3a=40 | | 2p^2-5p+2=0 | | 4k-2z=12 | | y-4y=-18 | | 10-3x+3=-2x-6x+3 | | 4x+11y=59 | | 3x-4y=-17 | | -7+3=-8y+7 | | 2x^2+3x+7=9 | | x^3=17 | | 8x+53-12= | | 4(2x+7)=3x-91 | | 12-7a+a^2=0 | | 2x+7=3x-91 | | y-4y=18 | | 8a^4-5a^2+4a^3= | | 5x-8=66 | | -5y-9=-4 | | 2a^2+22a+60= | | -6+3k=-4 |